2020
DOI: 10.1007/s00415-019-09690-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of disease-modifying therapy on peripheral leukocytes in patients with multiple sclerosis

Abstract: Modern disease-modifying therapies (DMTs) in multiple sclerosis (MS) have variable modes of action and selectively suppress or modulate the immune system. In this review, we summarize the predicted and intended as well as unwanted adverse effects on leukocytes in peripheral blood as a result of treatment with DMTs for MS. We link changes in laboratory tests to the possible therapeutic risks that include secondary autoimmunity, infections, and impaired response to vaccinations. Profound knowledge of the intende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 73 publications
(70 reference statements)
0
31
1
Order By: Relevance
“…However, the use of herpes antivirals was lower with rituximab compared to fingolimod and natalizumab; ocrelizumab clinical trials reported an increased risk of respiratory tract infections, 17,18 and safety issues emerged in diseases other than MS 19 . With respect to the association with treatment duration, it has been shown that long‐term anti‐CD20 treatment is associated with the risk of hypogammaglobulinemia in neuromyelitis optica‐spectrum disorder 20 . A protracted treatment may impact on the protective, anti–SARS‐CoV‐2 humoral response 21 and on a pre‐existing humoral and cellular immune repertoire, recently described in unexposed individuals 22,23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of herpes antivirals was lower with rituximab compared to fingolimod and natalizumab; ocrelizumab clinical trials reported an increased risk of respiratory tract infections, 17,18 and safety issues emerged in diseases other than MS 19 . With respect to the association with treatment duration, it has been shown that long‐term anti‐CD20 treatment is associated with the risk of hypogammaglobulinemia in neuromyelitis optica‐spectrum disorder 20 . A protracted treatment may impact on the protective, anti–SARS‐CoV‐2 humoral response 21 and on a pre‐existing humoral and cellular immune repertoire, recently described in unexposed individuals 22,23 …”
Section: Discussionmentioning
confidence: 99%
“…This preliminary result needs to be confirmed, but it is consistent with the idea that the immunological effects of ocrelizumab may last longer than 6 months. Reducing the frequency of dosing, or adjusting it according to the monitoring of B‐cell repopulation kinetics in individual patients, 20 may maintain efficacy while limiting the risk of infection 24 . A similar strategy deserves attention also in view of future vaccinations 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, prophylactic acyclovir therapy is recommended in patients experiencing a grade IV lymphopenia following CLAD. 29 As antibodies contribute to maintain protection from pathogens, inhibition of (intrathecal) antibody production is of special interest in the pathomechanisms involved in MS, where oligoclonal bands (OCBs) represent a hallmark. In fact, injectable CLAD was found to eliminate OCBs in 55% of pwMS, which in turn correlated with better clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…These kinetics suggest that patients receiving CLAD may be more prone to viral infections within the first 9 month of administration, which should be considered for clinical purposes. In this regard, prophylactic acyclovir therapy is recommended in patients experiencing a grade IV lymphopenia following CLAD 29 . As antibodies contribute to maintain protection from pathogens, inhibition of (intrathecal) antibody production is of special interest in the pathomechanisms involved in MS, where oligoclonal bands (OCBs) represent a hallmark.…”
Section: Discussionmentioning
confidence: 99%
“…Upon using cladribine for more than 4 months, a relevant decrease in circulating CD4 + T, NK cells, B cells, and T cells resulting in lymphopenia which makes COVID-19 patients more susceptible to infection severity and secondary infection. [44][45][46][47] The observed relevant immunosuppression actions following cladribine administration are mainly associated with higher infectious risk. [46,47] Several studies also suggest that cladribine treatments can be initiated in COVID-19 patients with demandable general health monitoring, but the risk-to-benefit ratio should be taken into consideration especially for aged immunocompromised patients.…”
Section: The Impact Of Immunotherapies In Managing Neurological Manifmentioning
confidence: 99%